CANONICAL QUANTIZATION OF THE GAUGED WESS-ZUMINO MODEL - Bowcock, P. (1989)
The canonical formalism is developed for the two-dimensional Wess-Zumino model on a group manifold G with a subgroup H⊂G gauged, using time as the evolution parameter. The system is a constrained hamiltonian system which is dealt with using Dirac's procedure. The theory is gauge fixed and quantised, and is found to be equivalent to the theory associated with the GKO coset construction for the coset G/H.